2013
DOI: 10.6061/clinics/2013(sup01)04
|View full text |Cite
|
Sign up to set email alerts
|

Update in the evaluation of the azoospermic male

Abstract: Approximately 1% of all men in the general population suffer from azoospermia, and azoospermic men constitute approximately 10 to 15% of all infertile men. Thus, this group of patients represents a significant population in the field of male infertility. A thorough medical history, physical examination and hormonal profile are essential in the evaluation of azoospermic males. Imaging studies, a genetic workup and a testicular biopsy (with cryopreservation) may augment the workup and evaluation. Men with nonobs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 43 publications
2
61
0
2
Order By: Relevance
“…Firstly, the 12.0% prevalence of azoospermia in the overall study group accords with the 10% -15% quoted by Gudeloglu and colleague [7] but much less than the 40% reported by Bashed et al [24] in Bangladesh. Earlier and recent studies have also shown decline in some semen quality with age [25] [26] such as lower ejaculate volume and sperm motility [27] [28] and increased paternal age with sperm quality [29].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Firstly, the 12.0% prevalence of azoospermia in the overall study group accords with the 10% -15% quoted by Gudeloglu and colleague [7] but much less than the 40% reported by Bashed et al [24] in Bangladesh. Earlier and recent studies have also shown decline in some semen quality with age [25] [26] such as lower ejaculate volume and sperm motility [27] [28] and increased paternal age with sperm quality [29].…”
Section: Discussionsupporting
confidence: 61%
“…Azoospermia may also occur because of a reproductive tract obstruction. A study has classified azoospermia into three primary categories: 1) pre-testicular, 2) testicular, and 3) post-testicular, speculating that, though 1) and 3) etiology of azoospermia are generally manageable, 2) is generally not [7]. Other studies suggested causes of male infertility, including azoospermia, as urogenital infections such as genito-urinary tract tuberculosis [8], or filarial orchitis [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expected values of FSH in normal men, is restricted between 1.0 -14.0 IU/l, in our hormonal analysis kit this fact observed in all of normozoospermia , OA and oligozoospermia but cryptozoospermia have marginal serum FSH value between upper normal limiting and abnormal value, OA have slightly lower FSH serum level than normozoospermia that agree with Ahmet G. et al, 2013 when said normal levels of FSH and LH are expected in OA; however, FSH and LH can be low or elevated in NOA (15) , this finding is matching the result of Yong-Tong Zhu et al,2016 when observed that FSH was remarkably elevated in Group NOA, moderate in Groups extremely sever oligozoospermia and cryptozoospermia ,and lowest in Group OA (16) . Other finding of this study is higher values of FSH were observed in the NOA that motivated with Bromage SJ.et al, 2007 when say the serum concentration of FSH is inversely correlated with the impairment of spermatogenesis (17) .…”
Section: Discussion:-supporting
confidence: 90%
“…In fact that, elevated levels of serum FSH with increasing severity of seminiferous epithelial destruction (16), which in teams is a reliable indicator of abnormal spermatogenesis in azoospermia patients. Moreover, it does not eliminate the possibility of obstruction and the capacity for fertility (17). Generally the occurrence of depressed spermatogenesis and elevated FSH levels seems to be a relatively good indicator for the presence of organic disorders of the testis (18).…”
mentioning
confidence: 99%